Behavior of Threading Dislocations from GaN Substrate to Epitaxial Layer. Issue 4 (26th February 2020) - Inotsume, Sho; Kokubo, Nobuhiko; Yamada, Hisashi; Onda, Shoichi; Kojima, Jun; Ohara, Junji; Harada, Shunta; Tagawa, Miho; Ujihara, Toru
Abstract : Threading dislocations (TDs) in the GaN substrate and homoepitaxial layer are nondestructively evaluated using X‐ray topography (XRT), Raman spectroscopy, and multiphoton photoluminescence (MPPL) imaging. When the XRT and Raman mapping images are compared, TDs in the GaN substrate are identified as threading edge dislocations (TEDs), threading mixed dislocations (TMDs), and threading screw dislocations (TSDs). TDs are observed to propagate from the GaN substrate to the epitaxial layer. From MPPL imaging, the TEDs are found to be inclined in the [ 1 1 ¯ 00 ] direction, which is at 90° from the Burgers vector. The TMD studied in detail is found to be inclined in the [ 1 ¯ 2 1 ¯ 0 ] direction, which is parallel to the Burgers vector. The feasibility of identifying TDs via analysis of the inclined direction of the dislocations in the GaN epitaxial layer is suggested. Abstract : The threading dislocations (TDs) in the GaN substrate and homoepitaxial layer are nondestructively evaluated. The TDs are observed to propagate from GaN substrate to the epitaxial layer. It is suggested that the TDs can be identified by analyzing the inclined direction in the GaN epitaxial layer from micro‐Raman mapping images.